Estrogen Is Renoprotective via a Nonreceptor-dependent Mechanism after Cardiac Arrest In Vivo - Hutchens, Michael P. (2010)
BACKGROUND: Severe ischemia induces renal injury less frequently in women than men. In this study, cardiac arrest and cardiopulmonary resuscitation were used to assess whether estradiol is renoprotective via an estrogen receptor (ER)-dependent mechanism. MATERIALS AND METHODS: Male and female C57BL/6 and ER gene-deleted mice underwent 10 min of cardiac arrest followed by cardiopulmonary resuscitation. Serum chemistries and renal stereology were measured 24 h after arrest. RESULTS: Estrogen did not affect mean arterial pressure, regional renal cortical blood flow, and arterial blood gases. Hence, female kidneys were protected (mean ± SEM: blood urea nitrogen, 65 ± 21 vs.149 ± 27 mg/dl, P = 0.04; creatinine, 0.14 ± 0.05 vs. 0.73 ± 0.16 mg/dl, P = 0.01; volume of necrotic tubules, 7 ± 1% vs. 10 ± 0%, P = 0.04). Estrogen also reduced renal injury. In intact females (n = 5), ovariectomized/vehicle-treated (n = 8), and ovariectomized/estrogen-treated (n = 8) animals, blood urea nitrogen was 65 ± 21, 166 ± 28, and 50 ± 14 mg/dl (P = 0.002); creatinine was 0.14 ± 0.05, 0.74 ± 0.26, and 0.23 ± 0.27 mg/dl (P = 0.014); necrotic tubules were 2.5 ± 0.25%, 12.0 ± 1.9%, and 5.0 ± 1.6% (P = 0.004), respectively. In ER-α and ER-β gene-deleted mice and controls estradiol-reduced functional injury (blood urea nitrogen: estradiol 117 ± 71, vehicle 167 ± 56, P = 0.007; creatinine: estradiol 0.5 ± 0.5, vehicle 1.0 ± 0.4, P = 0.013), but the effect of estradiol was not different between ER-α or ER-β gene-deleted mice. Adding ICI 182,780 to estradiol did not alter injury. CONCLUSIONS: In women, kidneys were protected from cardiac arrest through estrogen. Estradiol-mediated renoprotection was not affected by ER deletion or blockade. Estradiol is renoprotective after cardiac arrest. The results indicate that estradiol renoprotection is ER-α and ER-β independent.